Creative Community Spaces : Spaces That Are Transforming Cities into Innovation Hubs - Mulas, Victor; Nedayvoda, Anastasia; Zaatari, Ghia (World Bank, Washington, DC, 2017)
Communities of entrepreneurs are creating positive impacts on local economies. When they establish new businesses and innovate across industries, they bring about economic growth and employment. Entrepreneurs are generally drawn to cities because of their available resources and networks, specifically access to knowledge and sector-specific needs, and the exchange of information that occurs when an entrepreneurial community is brought together. Central to these ecosystems are creative community spaces (CCSs)—a range of physical spaces that enable innovation by creating a convening point for a community of entrepreneurs and start-ups. CCSs serve to anchor entrepreneurial communities and influence the urban economic and physical landscape.This report showcases a selection of 13 CCSs around the world that contribute to building a community that is sustainable and entrepreneurial and/or is helping advance an industry-specific or sectoral community. This report’s only intent is to showcase inspiring examples and models being implemented in diverse environments across the world. The authors hope this will help catalyze a conversation about the role of creative spaces in urban ecosystem development and provide policy makers as well as city innovation practitioners and private investors a better understanding of these spaces and how to leverage them effectively.